2017
DOI: 10.1002/cjoc.201600639
|View full text |Cite
|
Sign up to set email alerts
|

Chalcone‐Benzotriazole Conjugates as New Potential Antimicrobial Agents: Design, Synthesis, Biological Evaluation and Synergism with Clinical Drugs

Abstract: A series of chalcone-benzotriazole conjugates as new potential antimicrobial agents were synthesized and characterized by 1 H NMR, 13 C NMR, IR and HRMS spectra. Antimicrobial assay manifested that some target compounds gave moderate to good antibacterial and antifungal activities. The N-1 derived benzotriazole 5e and N-2 derived benzotriazole 6a exhibited valuable inhibitory efficacy against some tested strains. Especially, derivative 6a gave superior antifungal efficacies against C. utilis, S. cerevisiae and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 49 publications
0
2
0
2
Order By: Relevance
“…Por otro lado, las chalconas PLRC-2 y PLRC-3, de forma individual, presentaron efecto inhibitorio sobre el crecimiento de ambas bacterias, siendo más efectiva la PLRC-2. Estos resultados apoyan lo descrito por Wang, Li & Bi (2018), quienes mencionan reportan que el grupo carbonilo α,β-insaturado, la posición y la cantidad de los grupos hidroxilo que presentan los anillos aromáticos son factores importantes que causan también alteración en la estructura de bacterias como S. aureus y E. coli (Desai & Desai, 2003), lo que abre la posibilidad de investigar a estas chalconas como nuevos potenciales antibacterianos en el tratamiento de enfermedades infecciosas, haciendo mención que los estudios realizados frente a bacterias (Liu et al, 2017;Nielsen, Boesen, Larsen, Schønning & Kromann, 2004).…”
Section: Sustancia Evaluadaunclassified
See 1 more Smart Citation
“…Por otro lado, las chalconas PLRC-2 y PLRC-3, de forma individual, presentaron efecto inhibitorio sobre el crecimiento de ambas bacterias, siendo más efectiva la PLRC-2. Estos resultados apoyan lo descrito por Wang, Li & Bi (2018), quienes mencionan reportan que el grupo carbonilo α,β-insaturado, la posición y la cantidad de los grupos hidroxilo que presentan los anillos aromáticos son factores importantes que causan también alteración en la estructura de bacterias como S. aureus y E. coli (Desai & Desai, 2003), lo que abre la posibilidad de investigar a estas chalconas como nuevos potenciales antibacterianos en el tratamiento de enfermedades infecciosas, haciendo mención que los estudios realizados frente a bacterias (Liu et al, 2017;Nielsen, Boesen, Larsen, Schønning & Kromann, 2004).…”
Section: Sustancia Evaluadaunclassified
“…Los resultados obtenidos de esta investigación son preliminares y pioneros en la adición de chalconas sintetizadas a extractos etanólicos de propóleos para incrementar su actividad antibacteriana, pues solo se han realizado estudios utilizando antimicrobianos comerciales (Akca et al, 2016;Liu et al, 2017;Stepanović et al, 2003). Se observa que se presenta un sinergismo o antagonismo en la actividad antibacteriana en relación al microorganismo evaluado y la proporción utilizada entre el EEP y la chalcona, siendo necesarios estudios de los mecanismos de acción de estos compuestos y de la mezcla con el propóleo para el desarrollo futuro de compuestos clínicamente útiles como lo recomiendan Zhou & Xing (2015).…”
Section: Sustancia Evaluadaunclassified
“…Therefore, many increasing efforts were recently directed toward supramolecular species to explore their possible potential [ 11 , 13 ]. Azole heterocycles [ 14 , 15 , 16 ] such as imidazoles [ 17 , 18 , 19 ], triazoles [ 20 , 21 , 22 , 23 ], tetriazoles [ 24 , 25 ], thiazoles [ 26 , 27 , 28 ], oxazoles [ 29 , 30 ], benzimidazoles [ 31 , 32 ], benzotriazoles [ 33 , 34 ], and carbazoles [ 35 , 36 , 37 , 38 ] have been increasingly paid attention in recent years because they are the ideal building blocks for constructing supramolecular species due to their unique electron-rich aromatic structures with nitrogen, oxygen, and/or sulfur atoms that are capable of exerting multiple noncovalent bonds to form supramolecular species. These azoles were hybridized with sulfonamides [ 39 , 40 , 41 ], naphthalimides [ 42 , 43 , 44 ], coumarins [ 45 , 46 , 47 , 48 ], quinolones [ 49 , 50 , 51 ], quinazolones [ 52 , 53 , 54 ], berberines [ 55 ,…”
Section: Introductionmentioning
confidence: 99%
“…Ethenones, as a class of important natural drug scaffolds, showed unique fascination in the pharmaceutical field [ 25 , 26 ]. Ethenone serves as a bridging group that enables the increase of the conjugation system that facilitates inserting into DNA to prevent replication of bacterial DNA [ 27 , 28 ]. Furthermore, previous literature has shown that attachment of a benzonitrile via an olefinic bond at the 2-position of the quinazolinone can interact with the allosteric site of PBP2a, suggesting that large conjugated systems may be allosteric site-binding molecules for PBP2a [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%